Influence of microbial weathering on the partitioning of per- and polyfluoroalkyl substances (PFAS) in biosolids. Issue 3 (13th January 2023) - Lewis, Asa J.; Ebrahimi, Farshad; McKenzie, Erica R.; Suri, Rominder; Sales, Christopher M.
Abstract : Per- and polyfluoroalkyl substances (PFAS) are a large group of man-made fluorinated organic chemicals that can accumulate in the environment. Abstract : Per- and polyfluoroalkyl substances (PFAS) are a large group of man-made fluorinated organic chemicals that can accumulate in the environment. In water resource recovery facilities (WRRFs), some commonly detected PFAS tend to partition to and concentrate in biosolids where they can act as a source to ecological receptors and may leach to groundwater when land-applied. Although biosolids undergo some stabilization to reduce pathogens before land application, they still contain many microorganisms, contributing to the eventual decomposition of different components of the biosolids. This work demonstrates ways in which microbial weathering can influence biosolids decomposition, degrade PFAS, and impact PFAS partitioning in small-scale, controlled laboratory experiments. In the microbial weathering experiments, compound-specific PFAS biosolids–water partitioning coefficients ( K d ) were demonstrated to decrease, on average, 0.4 logs over the course of the 91 day study, with the most rapid changes occurring during the first 10 days. Additionally, the highest rates of lipid, protein, and organic matter removal occurred during the same time. Among the evaluated independent variables, statistical analyses demonstrated that the most significant solids characteristics that impacted PFAS partitioning were organic matter, proteins, lipids, and molecular weight of organics. A multiple linear regression model was built to predict PFAS partitioning behavior in biosolids based on solid characteristics of the biosolids and PFAS characteristics with a R 2 value of 0.7391 when plotting predicted and measured log K d . The findings from this work reveal that microbial weathering can play a significant role in the eventual fate and transport of PFAS and their precursors from biosolids.